GREEN MARKETING, CORPORATE SOCIAL RESPONSIBILITY, AND E-COMMERCE ADOPTION: THEIR INFLUENCE ON BRAND TRUST AND CUSTOMER LOYALTY IN INDONESIAN RETAIL BUSINESSES - Wulandjani , Harimurti; Siregar , Azijah Tussolihah; Faizah , Erna Nur; Hakim, Adi Lukman; Annas, Nafiz (Gapenas Publisher, 2025)
This study investigates the influence of green marketing, corporate social responsibility (CSR), and e-commerce adoption on brand trust and customer loyalty in Indonesian retail businesses. Using a quantitative approach, data were collected from 150 respondents through a five-point Likert scale questionnaire. Structural Equation Modeling – Partial Least Squares (SEM-PLS 3) was employed to analyze the relationships among the variables. The results show that green marketing, CSR, and e-commerce adoption significantly and positively affect brand trust, which in turn positively influences customer loyalty. Additionally, brand trust partially mediates the relationship between these independent variables and customer loyalty, highlighting its crucial role in fostering long-term consumer relationships. These findings provide practical insights for retail businesses in Indonesia to enhance sustainability initiatives, socially responsible practices, and digital adoption to strengthen consumer trust and loyalty.